2002
DOI: 10.1034/j.1399-3054.2002.1150305.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon assimilation, partitioning and export in mature cladophylls of two asparagus (Asparagus officinalis) cultivars with contrasting yield

Abstract: To assess the physiological aspects underpinning cultivar difference in asparagus (Asparagus officinalis L.) yield, diel carbon exchange, carbon partitioning and export and sucrose phosphate synthase (SPS) activity were examined in mature cladophyll tissue of two asparagus cultivars (ASP-69 and ASP-03) under field conditions. Both cultivars exhibited similar diel patterns in carbon exchange rate (CER) and carbohydrate partitioning. Rates of carbon export estimated from CER and dry mass changes were the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Among sucrose metabolizing enzymes, sucrose synthase (SS, EC 2.4.1.13) and invertase (EC 3.2.1.26) are involved in cleavage of sucrose whereas the enzyme sucrose phosphate synthase (SPS, EC 2.4.1.14) solely catalyzes sucrose biosynthesis (Guo et al 2002). The initial step in breakdown of sucrose is achieved by either invertase or sucrose synthase.…”
Section: Introductionmentioning
confidence: 99%
“…Among sucrose metabolizing enzymes, sucrose synthase (SS, EC 2.4.1.13) and invertase (EC 3.2.1.26) are involved in cleavage of sucrose whereas the enzyme sucrose phosphate synthase (SPS, EC 2.4.1.14) solely catalyzes sucrose biosynthesis (Guo et al 2002). The initial step in breakdown of sucrose is achieved by either invertase or sucrose synthase.…”
Section: Introductionmentioning
confidence: 99%
“…Acid invertase (AI), neutral invertase (NI), and sucrose synthase-cleavage (SS-cleavage) are the major enzymes responsible for sucrose decomposition 13 . Sucrose synthesis is catalyzed by synthase-synthesis (SS-synthesis) and sucrose phosphate synthase (SPS) 14 . Our previous studies on peach fruit demonstrated that low temperature stress causes a sharp decline in sucrose levels due to increased NI and AI activities 15 , if higher sucrose concentrations can be maintained, peaches are more tolerant to chilling injury 16 .…”
Section: Introductionmentioning
confidence: 99%
“…aAmylase catalyses hydrolytic cleavage of internal a-1,4-glucan bonds of starch releasing fragments that can be further broken down by b-amylase leaving a b-limit dextrin (Yang et al, 2001) while starch phosphorylase degrades starch by phosphorolytic cleavage to glucose 1-phosphate and is an enzyme used for the reversible phosphorylation of the aglucan in plant cells (Chen et al, 2002). Among the enzymes of sucrose metabolism, sucrose synthase and invertase are involved in sucrose-cleavage whereas sucrose phosphate synthase is the critical enzyme dedicated solely to sucrose biosynthesis (Guo et al, 2002). Invertases catalyse irreversible hydrolysis of sucrose to glucose and fructose (Hirose et al, 2002) whereas sucrose synthase (SS) is a cytosolic and reversible enzyme that catalyses sucrose degradation and supplies UDP-glucose and ADP-glucose for the synthesis of starch and cell wall polysaccharides (Baroja-Fernandez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%